Nowhere to Go: Parents' Descriptions of Children's Physical Activity During a Global Pandemic - Deanna Perez; Janelle K. Thalken; Nzubechukwu E. Ughelu; Camilla J. Knight; William V. Massey (Frontiers Media S.A., 2021)
Background: Schools and outdoor public spaces play a substantial role in children's physical activity. Yet, the COVID-19 shelter-in-place mandates bound many children to their available home spaces for learning, movement, and development. The exact effect this mandate had on children's physical activity may vary among families.Objective: To understand, from the perspective of parents, how the COVID-19 shelter-in-place mandates affected children's physical activity, while also considering families' socioeconomic status.Design: Open-ended survey.Setting: Online.Method: Data were collected from 321 parents living in the United States of America. Parents answered an open-ended prompt to describe their children's physical activity during COVID-19 shelter-in-place mandates. Following data collection, inductive and deductive content analysis examined patterns in the data.Results: Analyses indicated that shelter-in-place mandates restricted children's opportunities for physical activity. However, if families had access to outdoor spaces or equipment, they could encourage and support more physical activity opportunities than those without. Families in the lower-income bracket had less access to outdoor space and subsequently those children had fewer opportunities to be physically active. Parents supported their children's physical activity through their involvement and encouragement.Conclusion: These findings underscore the importance of access to outdoor spaces and equipment for increasing children's physical activity. Findings can be used by educators and policymakers to equitably support families of lower socioeconomic status who reported less access to outdoor spaces.